2009
DOI: 10.1002/crat.200800271
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of nano ZnS doped with Mn

Abstract: Nanocrystalline samples of Zn 1-x Mn x S (x = 0.0, 0.02, 0.04) were synthesized by chemical precipitation method and characterized for magnetism. EPR studies showed an evidence of ferromagnetism around room temperature. Hysterisis from vibrating sample magnetometer supports the observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(23 citation statements)
references
References 26 publications
0
22
0
1
Order By: Relevance
“…9a the hysteresis loop of undoped ZnS shows the diamagnetic behavior with some distortion. Antiferromagnetic with diamagnetic, Paramagnetic and Room temperature Ferromagnetic behavior of Mn doped ZnS nano particles have been reported [4,33,34]. It is reported that 3 and 5 % Mn doped hysteresis loop accommodates the shape of paramagnetic material.…”
Section: Magnetic Propertiesmentioning
confidence: 93%
“…9a the hysteresis loop of undoped ZnS shows the diamagnetic behavior with some distortion. Antiferromagnetic with diamagnetic, Paramagnetic and Room temperature Ferromagnetic behavior of Mn doped ZnS nano particles have been reported [4,33,34]. It is reported that 3 and 5 % Mn doped hysteresis loop accommodates the shape of paramagnetic material.…”
Section: Magnetic Propertiesmentioning
confidence: 93%
“…The results are summarized in Table 1. The results indicate that the doping of ZnS nanoparticles with nickel and copper ions was carried out at the desired mole fractions [22]. Fig.…”
Section: Characterization Of Nanoparticlesmentioning
confidence: 98%
“…Ferromagnetism (FM) in undoped sphalerite ZnS due to sulphur vacancies have been reported [3]. FM in ZnS with Curie temperature above room temperature in Co or Fe doped ZnS [4,5] nanoparticles (NPs); half metallic ferromagnetism in Cu doped ZnS [6,7]; possibility of long range FM ordering in ZnS:N through interaction of p electrons of N and S atoms [8] have been reported. Though Cr is a promising transition metal that can induce FM and luminescence simultaneously, studies on Cr doped ZnS are very few.…”
Section: Introductionmentioning
confidence: 97%